A simple method to detect plant based inhibitors of glycation induced protein cross-linking - Perera, HKI; Ranasinghe, HASK (Asian Journal of Medical Sciences, 2014)
Background: Glycation induced cross-linking of proteins are associated with chronic diabetic complications. Inhibition of protein glycation is one of the therapeutic approaches to prevent the progression of diabetic complications. Objective: Objective of this study was to establish a simple method to identify medicinal plants which can inhibit glycation induced protein cross-linking. Methods: Lysozyme was incubated at 37°C up to 4 weeks with different concentrations of glucose, fructose and ribose in sodium phosphate buffer (pH 7.4). Appropriate controls and blanks were carried out. Aminoguanidine (AG) was used as the standard inhibitor. Water extracts of Bryophyllum pinnatum leaves, Coriandrum sativum seed and Murraya koenigi leaves were used as potential inhibitors. Aliquots were removed from the incubation mixtures at intervals and analyzed for the presence of AGE induced protein cross-links, using SDS-PAGE. Appearance and the intensity of high molecular weight products were compared. Results: Extent of cross-linking was dependent on the sugar concentration. Cross-linking was slowest in the presence of glucose and fastest in the presence of ribose. AG inhibited glycation induced protein cross-linking in the presence of all three sugars. B. pinnatum leaves, C. sativum seeds and M. koenigi leaves inhibited protein cross-linking in the presence of sugar. This inhibition was greater than that of AG. Conclusions: We have established a simple SDS-PAGE method to identify medicinal plants which inhibit glycation induced protein cross-linking. We also demonstrated the effectiveness of B. pinnatum leaves, C. sativum seed and M. koenigi leaves in inhibiting glycation induced protein cross-linking in vitro. DOI: http://dx.doi.org/10.3126/ajms.v6i1.10181 Asian Journal of Medical Sciences Vol.6(1) 2015 28-33